Evolving Africa–EU relations: Changes in discourse from the Cotonou Agreement to the Samoa Agreement - Costa, C. M.; Yichao, L. (Canadian Journal of African Studies, 2025)
Established in 2000, the Cotonou Agreement reshaped the European Union’s engagement with the Organisation of African, Caribbean, and Pacific States (OACPS). OACPS members in Africa collectively represent the largest gross domestic product, population, and land area within the group. Negotiations on the Post-Cotonou Agreement concluded in April 2021. It was officially signed in November 2023 in Samoa, becoming known as the Samoa Agreement, and marked a significant juncture in EU–Africa relations. This study explores the need for this new agreement, focusing on why the EU and Africa (OACPS) required it. Additionally, we analyse the changes introduced in the Samoa Agreement compared to its predecessor(s) and evaluate their alignment with evolving political perspectives. Employing content and discourse analyses, our research unveils a resonance with African nations’ perceived needs and fundamental changes in the new document. This study offers insights into the evolving partnership between the EU and Africa.